Assessment of clinical benefit, cost and uptake of biosimilars versus reference biologics in immune-mediated inflammatory diseases in China - Xin Du; Xingxian Luo; Qixiang Guo; Qixiang Guo; Xiaomeng Jiang; Xiaomeng Jiang; Ziling Su; Weiting Zhou; Zhongjian Wang; Jiarun Li; Yue Yang; Yue Yang; et al. (Frontiers in Public Health)
BackgroundAs China is one of the countries with the highest recorded cases of Immune-Mediated Inflammatory Diseases (IMIDs), these diseases have also emerged as a serious public health concern. Biosimilars, potentially lower-cost versions of biologics, may improve access to more affordable yet comparably effective treatments. Encouragingly, China launched its abbreviated biosimilar pathway in 2015, and since then, a large number of biosimilars have been approved. However, systematic studies on the therapeutic efficacy and economic impact of IMIDs biosimilars are lacking in China. This study aims to assess the clinical benefits (including efficacy/effectiveness, safety, and immunogenicity), cost and uptake of adalimumab biosimilars, tocilizumab biosimilars, and infliximab biosimilars compared with their reference biologics in patients with IMIDs in China.MethodsIMIDs biosimilars and their reference drugs approved in China between 2015 and 2024 were identified. Head-to-head randomized clinical trials (RCTs) and real-world cohort studies on adalimumab, tocilizumab and infliximab and their biosimilars for the treatment of IMIDs were assessed. PubMed, Embase, Cochrane Library, Clinicaltrials.gov, and Listed Drug Database of China National Medical Products Administration were searched for clinical trials and cohort studies on biosimilars for IMIDs from their inception to November 1, 2024. We evaluated the monthly treatment costs and quarterly uptakes of these biosimilars and their reference biologics in China. Besides, we simulated the impact of biosimilar substitution in different scenarios. Meta-analyses were performed using a random-effects model to evaluate the efficacy, safety, and immunogenicity of treatments, including pooled risk ratios (RR) for ACR20 for rheumatoid arthritis, ASAS20 for ankylosing spondylitis, and PASI for plaque psoriasis, treatment-emergent adverse events (TEAEs), serious adverse events (SAEs), anti-drug antibodies (ADAs), and neutralizing antibodies (Nabs), with 95% credible intervals (CrIs).FindingsA total of 12 RCTs involving 5,717 patients with IMIDs were analyzed, including 12 approved biosimilars of adalimumab, infliximab, and tocilizumab. The primary endpoints of adalimumab (7 RCTs with 3,174 patients; RR, 1.02; 95% CrI, 0.99–1.06, p = 0.33), infliximab (3 RCTs with 1,291 patients; RR, 1.02; 95% CrI, 0.94–1.11, p = 0.98), tocilizumab (2 RCTs with 1,252 patients; RR, 1.01, 95% CrI, 0.94–1.08) met equivalence with reference biologics. Additionally, there was no significant difference between biosimilars and their reference biologics in the secondary endpoints. Overall, biosimilars demonstrated comparable safety (TEAEs: RR, 0.99; 95% CrI, 0.95–1.02, p = 0.44) (SAEs: RR, 0.80; 95% CrI, 0.42–1.54, p = 0.50) and immunogenicity (ADA: RR, 1.00; 95% CrI, 0.95–1.04, p = 0.85) (Nabs: RR, 0.93; 95% CrI, 0.82–1.05, p = 0.25) profiles to reference biologics. These findings were consistent with the cohort studies. In 2024, IMIDs biosimilars are available at 63 to 82% of the price per unit of the reference drugs, with uptake rates of 16.5 to 72.1% in China. Patients with IMIDs using these biosimilars could save between $874 and $2,184 per month in treatment costs, equivalent to 1.8 to 7.0 times the per capita monthly disposable income in China in 2024. Simulation showed that with 100% biosimilar substitution, savings would increase to $22.98 M, $33.83 M, and $3.82 M for adalimumab, infliximab, and tocilizumab, respectively. This would enable treatment for an additional 6,700, 9,863, and 4,373 patients, respectively.InterpretationOur study revealed that IMID biosimilars in China provide clinical benefits comparable to their reference biologics evidenced by high-quality RCTs and cohort studies with offer significant cost savings in China. Encouraging China’s national volume-based procurement and multi-stakeholder collaboration may help accelerate the substitution of IMIDs biosimilars.